Vertical growth and decay of convective cloud cells and associated precipitation rates at different levels (MAUSAM, 1961)
Study, using radar, has been made of history of growth and decay, in the vertical of convective rain cells around Delhi, and of associated variations in liquid water concentration of rate of precipitation release at different heights as judged from echo intensity measurements.  Data relating to three such situations, typifying respectively rain from (a) warm, (b) moderately cold and (c) very tall and highly supercooled (as in a severe thunderstorm) convective cloud are presented in the paper.  One common feature noticed, namely, that the rise of fall in precipitation rate at each level, follows closely a similar trend in variation of height of radar cloud top, needs to be given detailed consideration on the basis of suitable model of distribution of vertical currents within such a cell.  Some tentative considerations have been given to this aspect of the problem.